FIND PRICES AND MINIMUM DISTANCE IN NEAREST DELIVERY OF GOODS BY USING DYNAMIC PROGRAMMING - Rahmat Sigit Muliana; Hariyanto, Skom, MM Hariyanto, Skom, MM (Jurnal Sistem Informasi, 2000)
Writing consists of four chapters, where the first chapter explains the problem insending the goods back with the nearest distance routes and costs little.In the second chapter, the authors make the basic theories used to solve the problemsin the first chapter. In addition there are also explanations regarding the type ofprogram used by writers to assist in solving these problems with computer.Analysis of problems and their solutions are explained in the third chapter, where anexplanation of the method and manner completion problems with calculationsperformed using the method described in previous chapters.Here were also administered the program flow and design inputs and outputs aregiven an overview of program structure and the results ouputnya.The conclusion of this chapter is contained in chapter four is that saving time and costare important, even more so in the case of delivery of goods, so people always wantmore speed and efficiency. But for that should need to be taken into account also thevariables involved that can affect the desired final solution.